The Moxon Tennyson: Illustration and the Making of Meaning. A Contextualisation of the 1857 Illustrated Edition of Alfred Tennyson's Poems, Consisting of a Formal, Art Historical Investigation into its Designs and Engravings with a View to Assessing the Agency of the Image in the Reading of the Poetry - Vilhena, Larissa (Trinity College Dublin. School of Histories & Humanities. Discipline of History Of Art, 2024)
This doctoral thesis investigates the illustration in the illustrated edition of Alfred Tennyson's Poems (`The Moxon Tennyson') first published in 1857 by Edward Moxon. The 1857 edition contains a total of eighty poems, thirty-nine of which are accompanied by illustrations made up of varying pictorial styles and distinct illustrative approaches. Of the fifty-four illustrations in the book, twenty-four were designed by five leading Royal Academicians: the British artists Clarkson Frederick Stanfield, Thomas Creswick and John Callcott Horsley, and the Irish artists William Mulready and Daniel Maclise. The remaining thirty illustrations were created by three established Pre-Raphaelite artists, William Holman Hunt, Dante Gabriel Rossetti and John Everett Millais. The Moxon drawings were converted into wood engravings by professional engravers, namely the Brothers Dalziel, William James Linton, Thomas Williams, John Thompson, Charles Thurston Thompson and W. T. Green. Today the Moxon Tennyson is regarded as an exemplar of the Victorian gift book due to its popularisation of `high' arts (visual art and poetry) as the book was available and affordable to a wider readership, including the English middle classes, as well as the female reader. Despite the commercial failure of the volume at the time of publication, the diverse range of illustrations set a standard that numerous other illustrated volumes would strive to attain in the two decades following its publication in May 1857.
APPROVED
Keywords: illustration; poetry; Victorian; Tennyson; Moxon; Pre-Raphaelite; English